Obstacles to Enhancing Professional Development with Digital Tools in Rural Landscapes - Sarah Hunt-Baron; Kelly N. Tracy; Emily Howell; Rebecca Kaminski (Journal of Research in Rural Education, 2015)
This case study examines the use of online tools, including blogs, as a means of enhancing face-to-face professional development in writing instruction for teachers in rural districts. Since many rural districts serve large physical areas that are geographically distant from larger metropolitan areas and/or colleges and universities, teachers in these districts may have fewer professional development opportunities. This study examines the use of digital tools to offer continued support when a physical presence may not be feasible. Over the course of a year, middle and high school English language arts teachers in three rural districts in South Carolina received approximately 60 hours of face-to-face professional development in writing instruction. To increase communication and collaboration between teachers and professional development providers, as well as to offer ongoing support for teachers throughout the year, Google Sites with blogs were established for each district. Teachers reported primarily using the sites to download and review professional development materials. Results revealed only partial participation in blogging across districts. Blogs were used in several ways: to report implementation of strategies modeled through professional development, to refl ect on assigned readings, to express positive responses to the professional development, and to voice concerns over implementation. The authors discuss possible obstacles to both participation and collaboration via blogs, as well as the challenges rural settings may pose when using digital technology more broadly to support professional development.